Prevalence of blepharitis in adult patients in Bogotá, Colombia (2023)
Introduction: Blepharitis is defined as a chronic inflammation of the eyelid margin and is a common cause of eye irritation. Its chronic nature, multiple etiologies and coexistence with ocular surface diseases makes its management a challenge. Although blepharitis is considered a common condition in our population, there is not enough information reported in the literature about its epidemiology or the frequency of the risk factors associated. Aims and Objectives: This cross-sectional descriptive study was performed in Bogotá, Colombia, and it was designed to identify blepharitis prevalence, and frequency of subtypes. Results: Blepharitis diagnosis was made in 68% (n = 215) of the patients, of whom 12.6% (n = 27) presented anterior blepharitis, 31.6% (n = 68) marginal blepharitis and 55.8% (n = 120) posterior blepharitis. Conclusions: We believe that blepharitis is an underdiagnosed condition in our country and may be different than that in other regions. We consider important to establish the real prevalence in our population to raise awareness, encourage early diagnosis, establish a foundation for new studies that allow us to identify and stablish risk factors and, of course, to evaluate therapeutic alternatives. The strategy to improve the rate of diagnosis of blepharitis would be through the education of the visual health professional in identifying the characteristic symptoms and signs of any type of blepharitis in order to be able to make an accurate classification and treatment.